Identifikasi Struktur Lapisan Bawah Permukaan Daerah Manifestasi Emas Dengan Menggunakan Metode Magnetik Di Papandayan Garut Jawa Barat - Arifan Kahfi, Rian; Yulianto, Tony (BERKALA FISIKA, 2008)
A geophysical investigation has been done using magnetics method at Papandayan, Garut, West Java. The aims of this research are to interpret the sub-surface geology structure at Papandayan based on 2D modelling and geological information. Raw data processing was performed using IGRF (International Geomagnetics Reference Field) and diurnal variation correction to obtain total field magnetic anomaly. Upward continuation was performed at 150 meters height above reference spheroide for total field anomaly. Reduction to pole was performed to simplify interpretation process. Data acquired using Proton Precession Magnetometer (PPM) and Global Positioning System (GPS) Garmin during 3 days, which cover an area of 600 meter x 1100 meter and measurement spacing was 5 meter. Qualitative interpretation were done by upward continuation total field magnetic anomaly maps. While quantitative interpretation was done by 2D modelling by slicing upward continuation total field magnetic anomaly maps using Geomodel. It is interpreted that Papandayan sub-surface geology structure was controlled by tuff rock with susceptibilities 1 x 10-5 in emu system, andesite rock with susceptibilities 0.0135 in emu system, porphyry rock 0.010 in emu system, intrusion rock with susceptibilities 0.013 in emu system, sedimentary rock with susceptibilities 7 x 10-5 in emu system, and sedimentary rock with susceptibilities 8 x 10-5 in emu system. Porphyry rock as gold prospect is interpreted as alteration zone of silisification. Keyword: magnetics, gold, Papandayan.